2014
DOI: 10.3109/09286586.2014.988877
|View full text |Cite|
|
Sign up to set email alerts
|

Vision Screening by Teachers in Southern Indian Schools: Testing a New “All Class Teacher” Model

Abstract: A school vision screening program involving ACTs resulted in more efficient screening than a program involving STs at about a third of the cost and also improved compliance with hospital referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 4 publications
2
13
1
1
Order By: Relevance
“…As the availability of eye-care specialists can be limited in school settings, particularly in low- and middle-income countries, studies have investigated the use of teachers, nurses, certified medical assistants and key informants for the provision of screening and basic eye-care for children 20 , 21 , 29 , 51 54 , 56 , 58 , 60 , 62 . Several studies found that training teachers in vision screening enabled the provision of a good-quality 51 , 53 , 56 and cost–effective service, 53 while facilitating the opportunity to motivate spectacle use among students 54 . Two studies reported that the use of teachers as vision screeners did not create significant burdens on normal workloads, and in fact enhanced rapport with children and parents 50 , 56 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the availability of eye-care specialists can be limited in school settings, particularly in low- and middle-income countries, studies have investigated the use of teachers, nurses, certified medical assistants and key informants for the provision of screening and basic eye-care for children 20 , 21 , 29 , 51 54 , 56 , 58 , 60 , 62 . Several studies found that training teachers in vision screening enabled the provision of a good-quality 51 , 53 , 56 and cost–effective service, 53 while facilitating the opportunity to motivate spectacle use among students 54 . Two studies reported that the use of teachers as vision screeners did not create significant burdens on normal workloads, and in fact enhanced rapport with children and parents 50 , 56 .…”
Section: Resultsmentioning
confidence: 99%
“…A key policy-based facilitator to the prioritization of child eye-care is uptake and execution of a national eye-care plan, 50 , 53 , 61 and the inclusion of eye-care in school health policy 28 , 29 , 50 , 55 , 58 . Studies assessing the feasibility of school-based eye-care interventions, such as the targeting of trachoma in the United Republic of Tanzania, 58 vision screening in Peru, 30 South Africa 29 and Thailand, 56 and the provision of free spectacles in China, 39 noted that success was dependent on multidisciplinary support from health and education ministries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have mentioned performing refractions in schools and prescribing glasses to children, but fail to mention the method of refraction used. [ 6 14 25 ] Apart from cycloplegia, there are other factors that differ in camp settings and eye clinic settings that may adversely affect the accuracy of refraction and spectacle power dispensed. None of the above-mentioned studies discuss these parameters and adversities faced in the school camps.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 11 12 ] However, one of the limitations of this method is nonreporting of children to referral clinics, the rate of which varies from as low as 9% to as high as 88% in various studies. [ 10 13 14 ] On the other hand, performing refraction in the school or campsite allows for provision of spectacles to maximum number of affected children without losing them to follow-up. Although optometrist/refractionists have performed refraction and dispensed spectacles in schools in a number of studies,[ 5 15 16 ] the accuracy of refraction performed in makeshift rooms in schools has not been studied so far.…”
mentioning
confidence: 99%